Human-Wildlife Coexistence in Nepal: Evolution of Relief Policies and Practices - Dhakal, Bed Kumar; Subedi, Naresh; Lamichhane, Babu Ram; Kandel, Sanjay; Baral, Suraj; Bista, Manjit; Silwal, Thakur (Banko Janakari, 2026)
Human-wildlife conflict is increasing at an alarming rate despite government efforts and local community support, posing a threat to both humans and wildlife species. Relief support for people affected by wildlife induced damage is a widely applied post-conflict mitigation approach. We reviewed relief provisions from government (policies, act, regulation, directives and five-year plan) and non-government organisations, including CBD, FAO, IUCN, and relevant peer-reviewed articles. The relief program was initiated through the Buffer Zone program at periphery of Chitwan National Park. The Buffer Zone Management Committee of Chitwan formed under ‘Buffer Zone Management Regulations, 1996, piloted a relief distribution practice in 1998 for wildlife damage using the 50% of the park’s revenue provided to buffer zone as per the regulations. This relief provision was designed as a compassionate measure to secure local community support for protected area management, offering cash support for losses of livestock, crops or in cases of human casualties. The Government established a legal mechanism of relief support payments to victims for wildlife caused damage through the Directive related to distribution of relief for wildlife caused damage 2009 under the provision of the National Park and Wildlife Conservation Act, 1973, and its Regulations 1975. By incorporating one and half decades of lessons learnt, the most recent Directive was formulated in 2023 to provide relief support for damage caused by 16 wildlife species. Such a provision reduces economic risks to surrounding communities and is expected to minimize retaliatory killings of wildlife. The high number of human-wildlife conflict cases demands substantial financial resources, raising concerns about the long-term sustainability of such relief programs. This has prompted the exploration of alternative measures to minimize human wildlife conflict, including endowment funds and crop and livestock insurance.